Structural requirements of steroidal agonists of transient receptor potential melastatin 3 (TRPM3) cation channels. (February 2014) - Drews, A; Mohr, F; Rizun, O; Wagner, T F J; Dembla, S; Rudolph, S; Lambert, S; Konrad, M; Philipp, S E; Behrendt, M; Marchais‐Oberwinkler, S; Covey, D F; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Transient receptor potential melastatin 3 (TRPM3) proteins form non‐selective but calcium‐permeable membrane channels, rapidly activated by extracellular application of the steroid pregnenolone sulphate and the dihydropyridine nifedipine. Our aim was to characterize the steroid binding site by analysing the structural chemical requirements for TRPM3 activation. Experimental Approach Whole‐cell patch‐clamp recordings and measurements of intracellular calcium concentrations were performed on HEK293 cells transfected with TRPM3 (or untransfected controls) during superfusion with pharmacological substances. Key Results Pregnenolone sulphate and nifedipine activated TRPM3 channels supra‐additively over a wide concentration range. Other dihydropyridines inhibited TRPM3 channels. The natural enantiomer of pregnenolone sulphate was more efficient in activating TRPM3 channels than its synthetic mirror image. However, both enantiomers exerted very similar inhibitory effects on proton‐activated outwardly rectifying anion channels. Epiallopregnanolone sulphate activated TRPM3 almost equally as well as pregnenolone sulphate. Exchanging the sulphate for other chemical moieties showed that a negative charge at this position is required for activating TRPM3 channels. Conclusions and Implications Our data demonstrate that nifedipine and pregnenolone sulphate act at different binding sites when activating TRPM3. The latter activates TRPM3 by binding to a chiral and thus proteinaceous binding site, as inferred from the differential effects of the enantiomers. The double bond between position C5 and C6 of pregnenolone sulphate is not strictly necessary for the activation of TRPM3 channels, but a negative charge at position C3 of the steroid is highly important. These results provide a solid basis for understanding mechanistically the rapid chemical activation of TRPM3 channels.